Development of a multiplex one-step real-time RT-PCR assay for the simultaneous detection of eight viruses associated with febrile rash illnesses - Aili Cui; Shulei Wang; Qiang Zhang; Huiling Wang; Zhen Zhu; Aqian Li; Qinqin Song; Yanzhe Hao; Jilan He; Wenbo Xu; Yan Zhang (Elsevier, 2020)
Fever and rash illnesses (FRIs) are a series of common diseases with fever and rashes as clinical manifestations, most of which are caused by viral infection. The rashes of FRIs are generally nonspecific; therefore it is difficult to identify FRI-associated viruses solely based on clinical symptoms. To achieve rapid and accurate identification of FRI pathogens, a multiplex one-step real-time reverse transcription-polymerase chain reaction (RT-PCR) assay was developed and evaluated in this study. Primers and probes were selected for the detection of measles virus (MeV), rubella virus (RV), human enterovirus (EV), varicella-zoster virus (VZV), dengue virus (DENV), human parvovirus B19 (B19), Epstein-Barr virus (EBV), and human herpes virus 6 (HHV-6), which cover the most common pathogenic viruses of FRIs. Detection of the eight FRI-associated viruses, which was divided into two groups/tubes, was simultaneously performed under universal optimized reaction conditions in multiplex one-step real-time RT-PCR assay. The multiplex real-time RT-PCR showed high sensitivity and specificity in detecting the eight FRI-associated viruses. The limits of detection (LODs) for the eight viruses were in the range of 47-177 copies/reaction, and no cross reactions for the eight FRI-associated viruses were found in the multiplex assay. In addition, the results of the multiplex real-time RT-PCR assay were consistent with the results of a monoplex real-time RT-PCR assay and sequencing for clinical specimens obtained from FRI patients. With its advantages of high efficiency and rapid and accurate diagnosis, multiplex real-time RT-PCR was very feasible for the early diagnosis of FRI pathogenic viruses and would be of great help for the proper treatment, monitoring, and initiation of preventive measures for FRI cases.